Impact of different activation procedures on sodium hypochlorite penetration into dentinal tubules after endodontic retreatment via confocal laser scanning microscopy - Betul Gunes; Kübra Yeşildal Yeter; Yasin Altay (BMC, 2024)
Abstract Background Infected dentinal tubules are a possible source of bacteria that are responsible for the failure of root canal treatment. Therefore, disinfection of dentinal tubules by increasing the penetration of the irrigation solution is important for success in retreatment cases. This study utilized confocal laser scanning microscopy (CLSM) to assess and compare the impact of XPR, ultrasonic irrigation (UI) and sonic activation (SA) on NaOCl penetration into dentinal tubules following endodontic retreatment. Methods A total of forty mandibular premolars were enrolled in this investigation. Following root canal preparation up to ProTaper X3 file (30/0.07), root canals were obturated with gutta-percha and bioceramic root canal sealer with single cone technique. The root canal filling materials were removed using ProTaper nickel-titanium rotary retreatment files until the working length was reached. The retreatment procedure was finalized using the ProTaper Next X4 (40/0.06). The teeth were divided into four groups based on the irrigation activation technique: control (conventional needle irrigation), SA, UI and XPR. During the final irrigation procedure, Rhodamine B dye was introduced to 5% NaOCl for visualization via CLSM. Subsequent to image acquisition, the maximum penetration, penetration percentage, and penetration area were calculated. Data were statistically analyzed using the Kruskal-Wallis, Friedman, and Bonferroni Dunn multiple comparison tests through R software (p < 0.05). Results In the middle third, UI yielded a significantly higher penetration percentage than the control group (p < 0.05). The UI and XPR groups showed increased penetration percentages in the coronal and middle thirds compared with the apical third (P < 0.05). Maximum penetration was notably reduced in the apical third than in comparison with the coronal and middle thirds in all groups (p < 0.05). In the control, SA and XP groups, the penetration area was ranked in descending order as coronal, middle and apical (p < 0.05). Conversely, in the ultrasonic group, the penetration area was significantly lower in the apical third than in the middle and coronal thirds (p < 0.05). Conclusions UI enhanced the penetration percentage in the middle third of the root compared with that in the control group. XPR and SA showed no significant effect on NaOCl penetration following retreatment.